Workshop Evaluasi Program Siaran: Memadukan Perspektif Regulasi dan standar Teknis - Ilmi Sila Ayu; Febi Ramadhani Rusdin; Arief Yulianto; I gusti Ayu Aristi Putri (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The broadcasting industry in Indonesia faces significant challenges in ensuring that broadcast programs comply with regulations established by the Indonesian Broadcasting Commission (KPI) through the Broadcasting Code of Conduct and Broadcast Program Standards (P3SPS). This Community Service Program (PKM) aims to enhance the competencies of employees in the Program Operations Division, particularly in the Transcription and Programming sections of MNC Group, in evaluating the eligibility of broadcast programs. Through a workshop involving two communication science lecturers, this training integrates the regulatory perspective of P3SPS with technical audio-visual standards. The results of the activity indicate an improvement in participants' understanding of broadcasting evaluation principles and their ability to apply technical and regulatory standards in daily work.